Is there a reason why obese patients choose either conservative treatment or surgery? - Fischer, Lars; Wekerle, Anna-Laura; Nickel, Felix; Billeter, Adrian; Zech, Ulrike; Bruckner, Thomas; Müller, Beat P. (Obesity surgery, 2017)
BackgroundThe effects of bariatric surgery on excess weight loss (EWL) and comorbidities are proven. Still, a significant number of patients prefer conservative therapy (ConsP).ObjectivesThe goal of this study was to examine why ConsP and patients awaiting bariatric surgery (SurgP) choose which therapy, and to define the differences in their expectations.SettingProspective study, 1 university hospital, 1 general hospital, Germany.MethodsConsP and SurgP were asked to complete a questionnaire. Statistical analysis including all patients and a BMI-matched cohort was performed using the chi-square and Wilcoxon rank-sum test.ResultsOverall, 151 patients participated in this study (50 ConsP, 101 SurgP, 69.4% females). The mean age was 41.1 years (SD ± 12.2 years). ConsP had a significant lower body mass index (BMI, 44.7 kg/m2 vs. 49.3 kg/m2, p < 0.01). The educational level was significantly higher in ConsP. SurgP suffered significantly more often from depression (21.6% vs. 36.6%, p = 0.02) and joint pain (45.1% vs. 68.7%, p = 0.02). ConsP completed significantly more diets that were supervised by physicians or considered well-structured (56.3% vs. 31.0%, p = 0.04). SurgP considered their chosen therapy a last resort significantly more often (p < 0.01). A BMI-matched analysis between ConsP and SurgP revealed no significant differences in the prevalence of comorbidities but showed that fear of surgery plays a major role in the decision-making processes of obese patients.ConclusionA higher BMI and a greater prevalence of comorbidities had driven patients to seek a more radical solution for their obesity, i.e., surgery. The BMI-matched analysis suggests that fear of surgery is a relevant factor in why obese patients do not decide to undergo bariatric surgery lightly.